Homologous recombination is reduced in female embryonic stem cells by two active X chromosomes. (26th July 2021) - Tamura, Yuka; Ohhata, Tatsuya; Niida, Hiroyuki; Sakai, Satoshi; Uchida, Chiharu; Masumoto, Kazuma; Katou, Fuminori; Wutz, Anton; Kitagawa, Masatoshi
Abstract: The reactivation of X‐linked genes is observed in some primary breast tumors. Two active X chromosomes are also observed in female embryonic stem cells (ESCs), but whether double doses of X‐linked genes affect DNA repair efficiency remains unclear. Here, we establish isogenic female/male ESCs and show that the female ESCs are more sensitive to camptothecin and have lower gene targeting efficiency than male ESCs, suggesting that homologous recombination (HR) efficiency is reduced in female ESCs. We also generate Xist ‐inducible female ESCs and show that the lower HR efficiency is restored when X chromosome inactivation is induced. Finally, we assess the X‐linked genes with a role in DNA repair and find that Brcc3 is one of the genes involved in a network promoting proper HR. Our findings link the double doses of X‐linked genes with lower DNA repair activity, and this may have relevance for common diseases in female patients, such as breast cancer. Synopsis: Homologous recombination efficiency is reduced in female ESCs with two active X chromosomes. Double doses of X‐linked genes, including Brcc3, are responsible for the lower HR efficiency in female ESCs. HR efficiency is reduced in female ESCs that possess two active X chromosomes compared with male ESCs that have only one X chromosome. Lower HR efficiency results from double doses of X‐linked genes. X‐linked Brcc3 is one of the genes involved in a network that accomplishes proper HR. Coupling the double doses of X‐linked genes and lower HR efficiency may have relevance for female breast cancer patients, which can exhibit X reactivation. Abstract : Homologous recombination efficiency is reduced in female ESCs with two active X chromosomes. Double doses of X‐linked genes, including Brcc3, are responsible for the lower HR efficiency in female ESCs.